Trauma in the lives of parents experiencing severe perinatal mental illness - Isobel, Sophie (Frontiers in Psychiatry, 2024)
Background: The perinatal period is a time of 'high risk' for new and recurrent episodes of mental illness with 0.1-0.2% of birthing parents requiring admission to specialist mental health units in the months after birth. The prevalence and role of trauma in the lives of birthing parents (most commonly mothers) experiencing severe perinatal mental illness is not well known. Method: In a new perinatal mental health unit in Sydney Australia, a retrospective audit of trauma prevalence was undertaken using patient completed questionnaires and electronic medical record data. Descriptive analysis was undertaken. Results: Prevalence of trauma in the lives of mothers with severe mental illness was found to be higher than that reported in general or community mental health settings, with 76% of mothers reporting lifetime trauma exposure and 24% meeting criteria for complex PTSD.The majority reported trauma experiences likely to impact attachment and also reported difficulties in responding to their infants' cues and needs. Discussion: The findings suggest a need for more research, awareness, and consideration of the role of trauma in experiences of perinatal mental illness, with implications for developing trauma informed models for responding to parental mental illness.